The chaos of fatwas, its couses and ways of treatment: the UAE experience - Altaher, Mohammed Hassan Ali (Tanjong Malim, 2021)
The chaos of fatwas, its couses and ways of treatment: the UAE experience by Altaher, Mohammed Hassan Ali